Kepemilikan dan Pengolahan Tanah dalam Perspektif Hukum Tanah Adat - Tehupiory, Aarce; APHA, Journal Manager (Jurnal Hukum Adat Indonesia, 2018)
This study aims to analyze land ownership and processing and understand a sense of justice for indigenous peoples from the perspective of Customary Land Law. This study uses a conceptual approach in understanding the reality under study. In the concept of indigenous law regarding land is communalistic religious, which views that the Indonesian people always prioritize and prioritize the interests of the community. The results of the study indicate that (1) the existence of communal land is recognized in the provisions of several laws and regulations insofar as the existence is still there; (2) customary institutions can provide recommendations on land for each land use so that the existence and protection of customary rights and customary law communities can provide justice, legal certainty, legal protection for indigenous peoples by making special regulations for the needs of the local community in land dispute resolution ulayat can thus accommodate a diversity of local customary law provisions that are part of national land law. This study recommends that the role of local government is as a facilitator and coordinator of policy makers, regarding the existence of community land, with the principle of respecting human rights and the principles of state law.